Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Aplikasi Online Single Submission (OSS) di Desa Ngrimbi, Kecamatan Bareng - Kevin Nugraha Ramadhan; Mu’tassim Billah; Raden Muhammad Rusydan; Farah Farah; M.Ghifari Akmal Prayogo; Dwi Rafly Wibowo (CV. Aksara Global Akademia, 2023)
Legality has an important role for the progress of the business owned by all business actors, because legality is basically a form of granting permits granted by the authorities to every business actor in running their business. Legality itself is said to be important because it is used as evidence that the business being run or established is feasible and ongoing. People who do not understand the importance of business legality are a problem that causes many business actors who do not have business legality to support their business. The community service carried out by Group 10 KKN-T MBKM UPN